Factors Responsible For Rural Residential Water Supply Shortage In Southeastern Nigeria - Obeta, Michael Chukwuma; Nwankwo, Cletus Famous (Journal of Environmental Geography, 2015)
Efficient water supply is very crucial to sustenance of socio-economic growth, poverty attenuation, and food security. In most rural areas of developing countries including Nigeria water supplies are not commensurate with demand leading to a shortfall in water use and many people suffer from this scenario. This research investigated the factors responsible for rural residential water supply shortage in Southeastern Nigeria. Data were collected through the use of four mixed but complimentary methods namely questionnaire survey, interviews, focus group discussions and secondary data sources. The data generated were analyzed through the use of descriptive and inferential statistical tools. Principal Component Analysis was employed to combine the variables accounting for water supply shortage into a few underlying dimensions. The results indicated that physical environment and inadequate water supply infrastructure; socio-economic and geographical location; management and socio-cultural problems are responsible for water supply shortage in the area. Residential water supply can be sustainable in the area by regulating the influence of these factors impacting on water supply as well as lessen the implications of water deficiency. The research concludes that the process of water supply development should be stepwise in accordance with the participatory and managerial capacity of communities.